PERUMUSAN GARIS TANGGAL KAMARIAH INTERNASIONAL BERDASARKAN KONJUNGSI - Nur Anshari (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2017)
Inside knowledge more develop is following with demand periode is more develop too, Islamic Internasional Calendar become is theinevitability of concentrate Islamic date in world. Of course theproblem about that will be there in a row what is the concept in use,lunar date, matla’, visible or no to hilal, conjunction be valid.Necessary discourse is too long and comprehensive inside discussformulation Internasional Islamic Calendar. That matter was neededmany people dan necessary members of religious community not toavoided with develop knowledge. We hope in this paper will bringrepresentation what the concept Internasional Islamic Calendar indiscuss in agreement reached in the world